(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Water is an essential part of all living. Water is used in daily life, household works, and many people depend on open-source water like a pond, tube wells, municipal water supply, etc. Globalizations increase the industries which increase pollution level and also increase microbial contamination of water sources, which cause different types of infectious diseases. Fungus is the main agent of water contamination. Fungal species are diversified and grow in any substrate. A few experiments focus on calculating the world’s most respected species. There are millions of wide fungal species widely distributed throughout the world. India has always been an independent destination for this growth. Fungal biotechnology has developed as an essential part of human well-being. In the present study, the discovery and distribution of fungal species in different lake waters highlight the magnitude of their diversity and the uniqueness of their habitats. Water sample was collected from five ponds like Kachandur, Bhilai 3 Sitla Talab, Kurud, Junwani and Dhour located in different areas of Bhiali Durg City in Durg district of Chhattisgarh. The water sample was collected in March, April, July, August, November and December 2019. The water sample was analyzed for fungal diversity by the plating method of culturing potato dextrose agar media (PDA). The fungus isolated from the pond water sample includes species of Aspergillus (A. niger, A. fumigatus, A. oryzae) Penicillium species (P. notatum, P. chrysogenum) and also find out Rhizopus.).